2018
DOI: 10.1109/tmi.2017.2717958
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Imaging for Quantification of Vascular Stenoses: A Phantom Study

Abstract: Magnetic particle imaging (MPI) is a promising new tomographic imaging method to detect the spatial distribution of superparamagnetic iron-oxide nanoparticles (SPIOs). The aim of this paper was to investigate the potential of MPI to quantify artificial stenoses in vessel phantoms. Custom-made stenosis phantoms (length 40 mm; inner diameter 8 mm) with different degrees of stenosis (0%, 25%, 50%, 75%, and 100%) were scanned in a custom-built MPI scanner (in-plane resolution: ~1-1.5 mm and field of view: 65 29 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…MPI的高对比度和灵敏度, 通过采用低剂量的超顺磁 氧化铁纳米材料, Herz等人 [47] 准确定量了不同狭窄程 度的体外血管模型. Weizenecker研究组 [48] 则利用铁羧 葡胺作为示踪剂显示了搏动的小鼠心脏, 这个三维的 MPI在体研究结果表明, MPI在临床应用上又进了一 步, 在心脏外科有非常广阔的应用前景, 可用于先天性 心脏病的诊断、心脏结构缺失的判断等.…”
Section: Mpi在外科血管成像上显示出明显优势 得益于unclassified
“…MPI的高对比度和灵敏度, 通过采用低剂量的超顺磁 氧化铁纳米材料, Herz等人 [47] 准确定量了不同狭窄程 度的体外血管模型. Weizenecker研究组 [48] 则利用铁羧 葡胺作为示踪剂显示了搏动的小鼠心脏, 这个三维的 MPI在体研究结果表明, MPI在临床应用上又进了一 步, 在心脏外科有非常广阔的应用前景, 可用于先天性 心脏病的诊断、心脏结构缺失的判断等.…”
Section: Mpi在外科血管成像上显示出明显优势 得益于unclassified
“…As MPI features a high spatial resolution, it is interesting to be used for investigating the degree of stenosis [51]. By use of a stenosis phantom, which has a normal lumen of 10 mm diameter and allows a narrowing from 9 to 1 mm, referring to a stenosis degree of 19%–99%, the visualization of the stenosis degree with MPI was possible.…”
Section: Applications Of Mpimentioning
confidence: 99%
“…3 In the last decade, several studies demonstrated the potential of MPI for cardiovascular imaging and vascular interventions. [3][4][5][6][7][8] Most recently the proof of principle of MPI guided stent implantations and first safety measurements of stents became available. 9,10 Stent implantation is becoming increasingly common in clinical routine and interventional radiology and cardiology are steadily replacing surgical procedures.…”
Section: Introductionmentioning
confidence: 99%